The first case of osteoma of the mandibular notch located both medially and laterally and treated with a transoral endoscopy assisted approach. A case report. (2018) - Bocchialini, Gabriele; Bolzoni Villaret, Andrea; Negrini, Stefano; Tironi, Andrea; Salvagni, Luana; Castellani, Andrea
Highlights: This is the first case of an osteoma in the medial and lateral part of the sigmoid notch. Sigmoid notch osteomas are rare and this is only the seventh such case reported in the English literature. Surgical intervention was performed under general anaesthesia after nasal intubation with a transoral endoscopy assisted approach. Abstract: Introduction: Osteomas are slow-growing benign tumours composed of mature compact or cancellous bone and are seen in facial bones but uncommonly in the mandible; cases that arise in the notch region are rarely reported in the literature. Presentation of case: This article presents a 37-year-old woman with no preauricular swelling, no limitation of joint motion and pain only on the left side. Discussion: The patient was evaluated based on preoperative clinical manifestations, orthopantomography and a computed tomography (CT) scan. The CT scan showed bone density irregularity between the coronoid process and the left mandibular condyle in the notch region arising both medially and laterally. Surgery was performed based on these images and the patient's indications and symptoms. Conclusion: Among the cases of osteoma in the literature, only six originated in the mandibular notch, but this is the only that was both medially and laterally located.